Analysis of the Influence of Modern Retail Presence on Labor Absorption Local in Sumbawa Regency - Rahmadillah, Dita; Sahri, Sahri; Satarudin, Satarudin (West Science Journal Economic and Entrepreneurship, 2024)
This study aims to analyze "The Influence of Modern Retail Existence on the Absorption of Local Labor in Sumbawa Regency". It is a quantitative descriptive research design that is being employed. Time series data were the sort of data utilized in this investigation. The Panel Data Regression analysis approach was used in Eviews 10 to analyze the data. The study's findings demonstrate that the independent factors of Indomaret (X2) and Modern Retail Alfamart (X1) jointly affect the dependent variable of Local Labor (Y). The test findings indicate that there is a notable impact of Alfamart (X1) and Indomaret (X2) on the absorption of Local Workers (Y). The results of this test are known that each increase in one modern retail unit will directly affect the absorption of local labor of Alfamart (X1) of 9.141800 and Indomaret (X2) of 9.894077 units in Sumbawa Regency.